Climate Services for Agriculture in Rwanda Baseline Survey Report - Coulibaly, Jeanne Y.; Birachi, Eliud Abucheli; Kagabo, Desire M.; Mutua, Mercy M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
This report presents analysis of a baseline household survey for the Rwanda Climate Services for Agriculture project – a four-year, USAID-funded initiative that seeks to benefit Rwanda’s farming communities and national economy through climate services and improved climate risk management. The survey intends to provide a baseline assessment of the state of climate services among agricultural households in Rwanda. A random sample of 3,046 respondents was nationally surveyed in the all four provinces of the country and in the city of Kigali. A total of 52% of the sample were female respondents, while two-thirds of the households interviewed were male-headed households. The baseline includes outcome indicators related to access, use of climate information, channels of communication, behavioral change and perceived livelihood benefit/impact. The project evaluation will involve assessing changes over time in these benchmark indicators and eventually comparing the changes across beneficiaries and non-beneficiaries. A qualitative component of the evaluation will provide deeper insights into users’ decision making, behavioral change and any socially differentiated effect.